A kind of hot pressing forming PVC floor and preparation method thereof
Through the combination of modified PVC resin and modified glass fiber and other materials, combined with the hot press forming process, the heat resistance and safety problems of existing hot press forming PVC floors are solved, and efficient and safe hot press forming PVC floors are achieved. Preparation improves the physical performance and service life of the floor.
Patent Information
- Application Number
- CN202311671119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-12-07
AI Technical Summary
The existing hot-pressed PVC floors have problems such as high price, unresistance to high temperatures, flammable, high installation requirements and high maintenance requirements. At the same time, the release of chlorine in chlorinated PVC floors will cause harm to human health.
Using modified PVC resin, modified glass fiber, diphenyl isooctyl phosphate and other materials, pre-mixed by a mixer and extruded with twin screws, combined with a hot press forming process, a hot press forming PVC floor with excellent physical properties is prepared. Improve its heat resistance, impact resistance and wear resistance.
The heat resistance performance, cost reduction, safety enhancement, service life and production efficiency of hot-pressed PVC floors are achieved, and the release of hydrogen chloride gas is avoided, and the dual requirements for floor performance and health and safety are met.
Smart Images

Figure BDA0004593252530000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flooring, and in particular to a hot-pressed PVC flooring and a preparation method thereof. Background Art
[0002] The technical background of hot pressing forming floor can be traced back to the early 1980s. At that time, China began to introduce hot pressing forming process to make PVC floor. After continuous development, this kind of floor was gradually widely used in the mid-to-late 1990s.
[0003] Hot pressing is a common method for manufacturing PVC flooring. PVC flooring is a new type of lightweight floor decoration material that is very popular in the world today, also known as "lightweight flooring". It is a popular product in Europe, America, Japan and South Korea in Asia. It has been popular abroad. It has entered the Chinese market since the early 1980s. It has been widely recognized in large and medium-sized cities in China and is widely used, such as homes, hospitals, schools, office buildings, factories, public places, supermarkets, businesses, and other places. "PVC flooring" refers to flooring made of polyvinyl chloride materials. Specifically, it is made of polyvinyl chloride and its copolymer resin as the main raw materials, and fillers, plasticizers, stabilizers, colorants and other auxiliary materials are added. It is produced on a sheet-like continuous substrate through a coating process or by calendering, extrusion or extrusion process; PVC itself is not easy to burn, and has excellent weather resistance and dimensional stability. However, during the processing of PVC, there are thermal stability, insufficient impact toughness and poor processing performance. In order to improve these shortcomings, additives are often added to modify the PVC resin to improve the thermal stability and impact resistance of PVC products, so as to improve its defects in processing and use.
[0004] CN112428653B discloses a hot pressing method for PVC composite floor and PVC composite floor, and relates to the technical field of PVC composite floor. The hot pressing method for PVC composite floor is to hot press and bond the first material layer, the first adhesive layer, the PVC substrate, the second adhesive layer and the second material layer arranged in sequence from top to bottom, and the first adhesive layer and the second adhesive layer are both hot melt curing copolymer adhesive layers; the hot pressing and bonding process includes a heating stage and a cooling stage, and the temperature is gradually increased and the pressure is gradually increased in the heating stage, and the temperature is gradually decreased and the pressure is gradually decreased in the cooling stage. In the heating stage, the method of gradually increasing the temperature and gradually increasing the pressure is adopted to promote heat conduction; in the cooling stage, the method of gradually decreasing the pressure is adopted to ensure that the entire material reacts under pressure and does not curl, so as to achieve the purpose of one-step hot pressing. However, the hot pressing molded PVC floor disclosed in the patent still has the common problems of PVC floor, that is, the price is relatively high, it is not resistant to high temperature, it is flammable, and it has high installation requirements and high maintenance requirements.
[0005] CN114347601A discloses a high-stability hot-pressed floor and a preparation method thereof. The invention relates to the technical field of hot-pressed floor, and in particular to a high-stability hot-pressed floor, comprising a floor decorative layer and a substrate formed by hot pressing, wherein the substrate comprises the following raw materials: chlorinated PVC, calcium carbonate, stabilizer, internal lubricant, external lubricant, and processing aid. The invention uses chlorinated PVC as the main material to replace the original type 5 PVC resin powder, so that the product exhibits better stability than conventional PVC floor. Chlorinated PVC is obtained by further chlorinating PVC resin. Because the increase in chlorine content increases the content of polar elements in chlorinated PVC resin, its physical and mechanical properties, especially high temperature stability, high temperature deformation resistance, weather resistance, aging resistance and flame retardant properties are greatly improved compared with PVC. However, the chlorine in the chlorinated PVC floor will release toxic hydrogen chloride gas, which is harmful to human health. Specifically, this floor will release toxic gases such as hydrogen chloride when heated, which may cause irritation and damage to the respiratory tract, eyes and skin. Summary of the invention
[0006] The present invention provides a hot-pressed PVC floor, and the preparation steps are as follows, calculated by weight:
[0007] S1: pre-mix 20-33 parts of modified PVC resin, 10-20 parts of modified glass fiber, 3-5 parts of diphenyl ethyl phosphate, 5-10 parts of plasticizer, 5-8 parts of stabilizer, 20-30 parts of filler, 2-3 parts of internal lubricant, 2-3 parts of external lubricant, 3-5 parts of polyvinyl alcohol, 3-10 parts of processing aid, and 1-2 parts of antioxidant by a mixer, with a mixing speed of 800-1000 r / min and a mixing time of 20-30 min. The uniformly mixed raw materials are extruded by a twin-screw extruder and hot-pressed at 80-140° C. to form a PVC floor substrate.
[0008] S2: stack and pave a PVC floor substrate with a thickness of 3.0 to 5.4 mm and a PVC wear-resistant layer with a thickness of 0.1 to 1.0 mm;
[0009] S3 is hot-pressed at a temperature of 80 to 140° C. and a pressure of 10 to 20 MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor.
[0010] The modified PVC resin preparation method is as follows:
[0011] (1) adding vinyl chloride, an initiator, a chain extender, a dispersant, a granulating agent, a 20-40% by mass hydrogen peroxide aqueous solution, and a 20-40% by mass sodium hydroxide aqueous solution into water and mixing and stirring at a stirring rate of 400-600 r / min for 10-20 min;
[0012] (2) continuing to heat to 30-60° C., adding a 30-50% by mass sodium sulfide aqueous solution, and polymerizing at a pressure of 1-3 MPa to obtain ultra-high molecular weight polyvinyl chloride;
[0013] (3) In order to improve the use value of polyvinyl chloride, post-treatment must be carried out, that is, it must go through the steps of alkali washing, water washing and hot air drying; the purpose of alkali washing and water washing is to remove low molecular weight polymers mixed in the polymer and a small amount of remaining dispersant gelatin and other impurities, because these substances are substances that seriously affect the thermal stability of polyvinyl chloride; alkali treatment generally uses a sodium hydroxide aqueous solution with a concentration of 0.1-0.2%, controls the treatment temperature to 85-90°C, and uses an air compressor to blow for 1-2 hours. The free alkali is removed with water, and finally dried with hot air at about 70-90°C to obtain the modified PVC of the present invention.
[0014] The initiator is at least one of azobisisobutyronitrile, azobisisoheptylnitrile and di(2-ethylhexyl)peroxydicarbonate; more preferably, the initiator is azobisisobutyronitrile.
[0015] The chain extender is at least one of 1,4-butanediol, 1,6-hexanediol, diallyl phthalate, and diallyl maleate; more preferably, the chain extender is diallyl phthalate.
[0016] The dispersant is at least one of gelatin, polyvinyl alcohol and calcium alkylbenzene sulfonate; more preferably, the dispersant is gelatin.
[0017] The granulating agent is at least one of sorbitol laurate and n-butyl chloroformate; more preferably, the granulating agent is n-butyl chloroformate.
[0018] The ratio of the vinyl chloride, water, dispersant, granulating agent, 20-40% aqueous hydrogen peroxide solution, 20-40% aqueous sodium hydroxide solution and 30-50% aqueous sodium sulfide solution is 25-40:30-50:0.01-0.03:0.3-1:0.01-0.03:0.3-1:0.3-1; more preferably, the ratio of the vinyl chloride, water, dispersant, granulating agent, 20-40% aqueous hydrogen peroxide solution, 20-40% aqueous sodium hydroxide solution and 30-50% aqueous sodium sulfide solution is 33:50:0.02:0.5:0.02:0.5:0.5.
[0019] The mass fraction of the aqueous hydrogen peroxide solution is 20-40%; more preferably, the mass fraction of the aqueous hydrogen peroxide solution is 30%.
[0020] The mass fraction of the sodium hydroxide aqueous solution is 20-40%; more preferably, the mass fraction of the sodium hydroxide aqueous solution is 30%.
[0021] The mass fraction of the sodium sulfide aqueous solution is 30-50%; more preferably, the mass fraction of the sodium sulfide aqueous solution is 50%.
[0022] The mass ratio of the vinyl chloride, initiator and chain extender is 20-40:5-8:1-2; more preferably, the mass ratio of the vinyl chloride, initiator and chain extender is 33:6.6:1.4.
[0023] The modified glass fiber preparation method is as follows, in parts by weight:
[0024] X1: immerse 10 to 20 parts of glass fibers in 50 to 100 mL of a 3 to 5% hydrofluoric acid aqueous solution for 20 to 50 seconds, continue to clean and dry them for later use;
[0025] X2: Mix the glass fiber of step X1 with 2 to 3 parts of alkoxysilane, 1 to 2 parts of end-capping agent, 50 to 100 mL of organic solvent, and 1 to 2 parts of catalyst at 40 to 80° C. for 2 to 3 hours to obtain modified glass fiber containing vinyl.
[0026] The glass fiber has a diameter of 20 to 60 μm and a length of 50 to 300 mm; more preferably, the glass fiber has a diameter of 40 μm and a length of 100 mm.
[0027] The alkoxysilane is at least one of dimethoxymethylvinylsilane, vinyltriethoxysilane, acryltriethoxysilane and phenyltriethoxysilane; more preferably, the siloxysilane is dimethoxymethylvinylsilane.
[0028] The end-capping agent is at least one of hexamethyldisiloxane, methyltriethoxysilane and tetramethyldivinyldisiloxane; more preferably, the end-capping agent is methyltriethoxysilane.
[0029] The organic solvent is at least one of tetrahydrofuran, methanol, toluene, n-hexane and chloroform; more preferably, the organic solvent is toluene.
[0030] The catalyst is at least one of sulfuric acid, phosphoric acid, hydrochloric acid and perchloric acid; more preferably, the catalyst is phosphoric acid.
[0031] The catalyst molar concentration is 0.8-2.5 mol / L; more preferably, the catalyst molar concentration is 1.0 mol / L.
[0032] The plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, polybutylene adipate, polybutylene adipate-1,4-adipate, chlorinated paraffin, epoxidized soybean oil, and 3-hydroxy-3-carboxytributyl glutarate; more preferably, the plasticizer is dibutyl phthalate.
[0033] The stabilizer is at least one of a calcium zinc stabilizer, a rare earth stabilizer, and an organic tin stabilizer; more preferably, the stabilizer is a calcium zinc stabilizer.
[0034] The filler is at least one of calcium oxide, calcium carbonate, precipitated barium sulfate and silicon dioxide; more preferably, the filler is calcium carbonate.
[0035] The internal lubricant is at least one of chlorinated paraffin and triacetylhydroxystearate; more preferably, the internal lubricant is chlorinated paraffin.
[0036] The external lubricant is at least one of stearic acid, silicone powder, methyl stearate, propyl stearate, and butyl stearate; more preferably, the external lubricant is stearic acid.
[0037] The processing aid is at least one of acrylic copolymers, chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymers, and vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomers; more preferably, the processing aid is vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer.
[0038] The antioxidant is at least one of antioxidant 1010, antioxidant 168, 2,6-di-tert-butyl-p-cresol, N,N'-di-sec-butyl-p-phenylenediamine, and trisnonylphenyl phosphite; more preferably, the antioxidant is trisnonylphenyl phosphite.
[0039] The functions of the main raw materials in the present invention are introduced as follows:
[0040] Modified PVC resin: In the present invention, the modified PVC resin refers to ultra-high molecular weight PVC resin, and the performance of ultra-high molecular weight polyvinyl chloride is better than that of polyvinyl chloride. As for the influence of the heat resistance of PVC resin, the greater the degree of polymerization of PVC, the better its heat resistance and the worse its processing performance, but the other ingredients added make up for the disadvantage of poor processing performance. Ultra-high molecular weight polyvinyl chloride (UHMWPVC) generally has an average degree of polymerization of more than 2000, a K value of more than 80, and an average molecular weight of about 150,000 to 200,000. Due to the high molecular weight, the number of entanglement points between the molecular chains of UHMWPVC increases, forming a similar cross-linked structure, so it has excellent physical properties, high tensile strength, high elongation at break, excellent fatigue resistance, wear resistance, heat resistance, solvent resistance, good compression and impact resilience, low compression permanent deformation, and a wide operating temperature range. UHMWPVC has good heat resistance, large molecular weight, and many entanglement points between molecular chains. Improve the processing performance of PVC resin and make the melt have better fluidity; improve the physical and chemical properties of PVC products, such as tensile strength, elongation at break, bending strength, weather resistance, etc.; reduce the cost of PVC products. Initiator azobisisobutyronitrile: The role of the initiator azobisisobutyronitrile in the synthesis of macromolecular polyvinyl chloride is to initiate free radicals and promote the growth of the polymerization chain. In the synthesis of polyvinyl chloride, azobisisobutyronitrile can decompose to produce free radicals, which can combine with vinyl chloride monomer to form a monomer initiator. Then, the monomer initiator can undergo a chain growth reaction with the vinyl chloride monomer to form a polyvinyl chloride macromolecule.
[0041] Chain extender diallyl phthalate: The mechanism of action of diallyl phthalate (DAP) as a chain extender in the synthesis of ultra-high molecular weight polyvinyl chloride (UHMWPVC) mainly involves the following aspects: 1. Chain extension: DAP, as a chain extender, can react with vinyl chloride (VCM) monomer to form diallyl ester. This diallyl ester, as an active center, can continue to react with VCM to generate longer polymer chains. This chain extension process can continue until the desired molecular weight and molecular weight distribution are obtained; 2. Branching reaction: In addition to chain extension, DAP can also undergo branching reactions with polyvinyl chloride chains. This branching reaction can increase the stereo conformational complexity of the polymer, thereby improving its mechanical properties. By controlling the degree of branching and the position of branching, the performance of the polymer can be optimized; 3. Molecular weight distribution control: Using DAP as a chain extender, the molecular weight distribution of the polymer can be controlled. By adjusting parameters such as the amount of DAP and the reaction temperature, ultra-high molecular weight polyvinyl chloride with a narrow molecular weight distribution can be obtained. This polymer has better processing performance and mechanical properties. 4. Thermal stability: DAP, as a chain extender, can also improve the thermal stability of polymers. At high temperatures, DAP can form a network structure to limit the movement of polymer chains, thereby reducing the possibility of thermal degradation. This improvement in thermal stability helps to improve the stability of UHMWPVC during processing and use.
[0042] In summary, the mechanism of action of diallyl phthalate as a chain extender in the synthesis of ultra-high molecular weight polyvinyl chloride mainly includes chain growth, branching reaction, molecular weight distribution control and thermal stability improvement. By rationally regulating these factors, UHMWPVC materials with excellent performance can be obtained.
[0043] Modified glass fiber: Modifying glass fiber from the perspective of chemical modification can make the glass fiber and the matrix interface bond better, so as to obtain a composite material with improved comprehensive performance such as impact strength, tensile strength and wear resistance. Therefore, the composite material is applied to high-strength and wear-resistant composite materials in flooring, which has extensive economic and social value. The surface of glass fiber is connected with long chains of polyvinyl chloride through chemical bonds; after corroding the glass fiber, it is found that the strength of the composite material is improved by glass fiber; long molecular chains of polyvinyl chloride are produced on the surface of glass fiber, and this structure is similar to the shape of a feather duster. The long chains of polyvinyl chloride are distributed on the surface of glass fiber like chicken feathers, so that the long-chain polyvinyl chloride on the surface of glass fiber after processing has good compatibility with polyvinyl chloride matrix resin, unlike ordinary glass fiber that can hardly be fused with the matrix, and unlike conventional silane coupling agent for surface modification of glass fiber, only a small amount of shorter chemical bonds are grafted on the surface of glass fiber, so that glass fiber cannot be completely compatible with polyvinyl chloride matrix.
[0044] Diphenyl isooctyl phosphate: Diphenyl isooctyl phosphate can effectively improve the toughness, hydrophilicity, stretchability and heat resistance of modified polyvinyl chloride. Diphenyl isooctyl phosphate and modified polyvinyl chloride have good compatibility. Diphenyl isooctyl phosphate (DPOP) is a commonly used industrial colorless, transparent, oily liquid plasticizer with good compatibility with polymers. The addition of diphenyl isooctyl phosphate can effectively improve the flexibility, hydrophilicity and thermal stability of polyvinyl chloride plastics. The higher the mass fraction of diphenyl isooctyl phosphate, the better the flexibility of the modified polyvinyl chloride sample, the stronger the hydrophilicity of the modified polyvinyl chloride film, and the stronger the thermal stability. Diphenyl isooctyl phosphate can change the glass transition temperature of modified polyvinyl chloride. In general, diphenyl isooctyl phosphate (C 20 H 27 O4P) is a colorless, transparent, oily liquid, mainly used as a flame retardant plasticizer. It is compatible with almost all major industrial resins and rubbers, and has better compatibility with modified polyvinyl chloride. It has low volatility, good plugging resistance and weather resistance. When used in combination with phthalate plasticizers, it can improve the toughness and weather resistance of the product; when used in modified polyvinyl chloride films, it can improve tensile strength and improve wear resistance and moisture resistance.
[0045] Plasticizer dibutyl phthalate: Reduces the flow temperature and melt viscosity of PVC, making it easier to process. Improves the cold resistance and impact resistance of PVC, making the PVC flooring more flexible and processable. In general, DOP plays an important role in the manufacturing process of PVC flooring. It can make PVC flooring softer and easier to process, while improving its cold resistance and impact resistance. Its mechanism is to weaken the attraction between polymer molecules, making it easier for polymer molecules to move, so that the PVC resin can undergo a glass transition at a lower temperature, thereby increasing the plasticity of the polymer.
[0046] Calcium zinc stabilizer: 1. Capture free radicals and inhibit oxidation reactions: Calcium zinc stabilizer can combine with degraded PVC macromolecular free radicals to form substances that cannot react with O2, thereby hindering oxidation reactions and improving the weather resistance and thermal stability of PVC; 2. Addition reaction with polyene structure to destroy the formation of large conjugated system and reduce coloring: The salt or ester of unsaturated acid contains double bonds, which can react with the conjugated double bonds in PVC molecules to undergo diene addition reaction, destroy its conjugated structure, reduce coloring, and improve the weather resistance of products; 3. Absorb and neutralize HCl to inhibit its autocatalytic effect. Calcium zinc stabilizer can react with HCl to inhibit the reaction of PVC dehydrogenation, and improve the weather resistance and thermal stability of PVC; 4. Replace the unstable allyl chlorine atoms in PVC molecules to inhibit the de-PVC: Organic tin calcium zinc stabilizer can coordinate with the unstable chlorine atoms of PVC molecules. In the ligand, organic tin replaces the unstable chlorine atoms, thereby improving the weather resistance and thermal stability of PVC. In addition, calcium zinc stabilizer can also improve the fluidity and processing properties of plastics, improve the processing efficiency and product quality of plastics.
[0047] Filler calcium carbonate: 1. Increase volume: Calcium carbonate as a filler can increase the volume of PVC products and reduce production costs; 2. Enhance stiffness and hardness: Calcium carbonate can increase the stiffness and hardness of PVC floors and improve the wear resistance of floors; 3. Improve dimensional stability: Calcium carbonate can serve as the skeleton of PVC floors and has a positive effect on the dimensional stability of floors; 4. Reduce thermal expansion and contraction coefficient: Calcium carbonate can reduce the thermal expansion and contraction coefficient of PVC floors, making them more stable when the temperature changes; 5. Improve impact resistance: Calcium carbonate can absorb and disperse impact force and improve the impact resistance of PVC floors; 6. Improve processing fluidity: Calcium carbonate can improve the processing fluidity of PVC floors and improve production efficiency.
[0048] Internal lubricant chlorinated paraffin: 1. Reduce melt viscosity: During the processing of PVC sheets, chlorinated paraffin can reduce the viscosity of PVC melt, making the melt more fluid and easier to process; 2. Reduce friction: chlorinated paraffin can form a lubricating film on the surface of PVC sheets, reducing the friction between PVC melt and processing equipment, reducing energy consumption, and extending the service life of equipment; 3. Promote dispersion: chlorinated paraffin also has the function of promoting the dispersion of other additives in PVC sheets, making the distribution of additives more uniform and improving the performance of PVC sheets. In general, chlorinated paraffin plays an important role as a lubricant in the processing of PVC sheets. It can reduce melt viscosity, reduce friction, and promote dispersion, thereby improving the processing performance of PVC sheets.
[0049] External lubricant stearic acid: 1. It can improve processing efficiency, prevent and overcome sheet adhesion, thereby improving the smoothness and gloss of the finished product and improving the appearance; 2. Stearic acid is also used as a dispersant for concentrated color masterbatches of various thermoplastic resins and a lubricating dispersant for filler masterbatches and degradation masterbatches, which can improve the processing performance, surface gloss, lubricity and thermal stability of PVC; 3. Stearic acid can also be used as a lubricant to enhance the diffusion of fillers and increase the rate of hot pressing.
[0050] Polyvinyl alcohol: Polyvinyl alcohol molecules have high adhesion and are easy to form films. The formed films are colorless and transparent, have good mechanical properties, a smooth surface without stickiness, and good solubility resistance. Polyvinyl alcohol can be used as an adhesive. First, the aqueous solution of polyvinyl alcohol has extremely strong adhesion to materials containing cellulose, and has the advantages of safety and non-toxicity; secondly, polyvinyl alcohol can generate polyvinyl alcohol condensation products with stronger water resistance, adhesion, and mechanical strength under acid catalysis. Finally, polyvinyl alcohol can be used as a surface sizing agent, which has good film-forming properties and high film strength, and can improve the wear resistance, oil resistance, and smoothness of PVC sheets.
[0051] Processing aid vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer: VCE for short, can toughen and modify PVC resin to improve the impact resistance of polyvinyl chloride, and can improve the tensile strength and bending strength of PVC. At present, the main impact modifiers for PVC resin are MBS, ACR, and CPE. VCE is one of the most important impact modifiers for PVC. Its structure is a core-shell structure. While toughening PVC, it maintains the transparency of PVC to the maximum extent and improves the impact resistance of PVC. With the increase of VCE addition content, the impact strength of PVC composite materials increases, the heat deformation temperature decreases, and the elongation at break increases; under the same conditions, the effect of VCE modified PVC is better than that of ACR, CPE and MBS. VCE is evenly dispersed in the continuous phase of the PVC matrix in the form of particles. The vinyl chloride chain segment is combined with PVC, and the elastic butyl acrylate chain segment acts as a stress concentration center. On the one hand, it induces a large number of silver streaks to form shear bands. The generation and development of a large number of silver streaks and shear bands consume a lot of energy, thereby improving the impact resistance of PVC resin; on the other hand, the butyl acrylate chain segment can absorb the impact energy and transfer it to the surrounding PVC resin, controlling the development of silver streaks and terminating them in time so that they do not develop into destructive cracks, thereby achieving the effect of resisting crack development and improving the toughness of PVC resin.
[0052] Antioxidant trisnonylphenyl phosphite: in PVC flooring, it delays or inhibits the oxidative degradation of PVC, enhances the stability of PVC, improves the color and weather resistance of the product, and extends the service life of the PVC flooring. Adding antioxidants to PVC sheets can play an antioxidant role, thereby extending its service life. Antioxidants can prevent PVC sheets from undergoing oxidation reactions under the influence of factors such as ultraviolet rays, oxygen and moisture, thereby reducing their strength and performance. There are many types of antioxidants, and commonly used ones include phosphites, thio compounds, and the like. The antioxidant trisnonylphenyl phosphite used in the present invention belongs to the phosphite antioxidant class, and phosphites have a good effect. They can be embedded in the molecular chain of the PVC board to prevent the occurrence of oxidation reactions.
[0053] Beneficial effects of the present invention:
[0054] 1. The modified PVC of the present invention has a large degree of polymerization and good heat resistance. Since the modified PVC has a large molecular weight, the number of entanglement points between PVC molecular chains increases, forming a similar cross-linked structure. Because it has excellent comprehensive physical properties, it has high tensile strength, high elongation at break, excellent fatigue resistance, wear resistance, weather resistance, heat resistance, solvent resistance, good compression and impact resilience, low compression permanent deformation, and a wide operating temperature range.
[0055] 2. The present invention adds polyvinyl alcohol to the modified PVC resin, thereby improving the anti-scratch and anti-wear properties of the floor.
[0056] 3. The modified PVC prepared by the present invention has excellent performance due to the addition of modified glass fiber.
[0057] 4. The laminating process of the substrate and the wear-resistant layer of the hot-pressed PVC floor of the present invention is convenient, has a stable production process and production efficiency, and can be produced in large quantities. DETAILED DESCRIPTION
[0058] In order to further understand the present invention, a hot-pressed PVC floor and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.
[0059] In the following statements:
[0060] PVC resin: Model SG-8, K value is 59-55, average degree of polymerization is 750-650, viscosity is 86-73 ml / g, source: Shandong Dezhou Shihua Chemical Co., Ltd.
[0061] PVC wear-resistant layer: Model: 1FDTSX, source: Nan Ya Plastic Industry (Nantong) Co., Ltd.
[0062] Gelatin: Model: S30952, source: Shanghai Yuanye Biotechnology Co., Ltd.
[0063] Calcium zinc stabilizer: Model: WD-7, source: Qingdao Gabet New Material Technology Co., Ltd.
[0064] Chlorinated paraffin: Model is medium-chain chlorinated paraffin 52, source: Anhui Xingxin Materials Technology Co., Ltd.
[0065] Calcium carbonate: particle size is about 15μm.
[0066] Vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer: VCE for short, homemade, preparation method refers to the preparation of VCE-3020 in "Yang Kang et al. Preparation and performance study of vinyl chloride copolymer elastomer [J]. Materials and Properties, 2016, 44(6): 18-23".
[0067] The glass fiber has a diameter of 40 μm and a length of 100 mm;
[0068] Polyvinyl alcohol: Model: PVA-217, source: Guangzhou Ketai Chemical Co., Ltd.
[0069] Example 1
[0070] A method for preparing a hot-pressed PVC floor comprises the following steps:
[0071] S1: pre-mix 33g of modified PVC resin, 17g of modified glass fiber, 3.3g of diisooctyl phthalate, 7.0g of dibutyl phthalate, 6.1g of calcium zinc stabilizer, 27.5g of calcium carbonate, 2.2g of chlorinated paraffin, 2.2g of stearic acid, 5.0g of polyvinyl alcohol, 8.0g of vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer, and 1.1g of trinonylphenyl phosphite by a mixer at a mixing speed of 900r / min and a mixing time of 20min. The uniformly mixed raw materials are extruded by a twin-screw extruder and hot-pressed at 90°C to obtain a PVC floor substrate;
[0072] S2 is to stack and pave a PVC floor substrate with a thickness of 3.9 mm and a PVC wear-resistant layer with a thickness of 0.6 mm;
[0073] S3 is hot-pressed at a temperature of 90°C and a pressure of 13MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor; the density is 1.8g / cm 3 .
[0074] The preparation method of the modified PVC resin is:
[0075] (1) 33 g of vinyl chloride, 6.6 g of azobisisobutyronitrile, 1.4 g of diallyl phthalate, 0.02 g of gelatin, 0.5 g of n-butyl chloroformate, 0.02 g of a 30% aqueous hydrogen peroxide solution, and 0.5 g of a 30% aqueous sodium hydroxide solution were added to 50 mL of water and mixed at a stirring rate of 400 r / min for 10 min.
[0076] (2) continuing to heat to 38° C., adding 0.5 g of a 50% sodium sulfide aqueous solution, and polymerizing at a pressure of 2 MPa to obtain ultra-high molecular weight polyvinyl chloride;
[0077] (3) In order to improve the use value of polyvinyl chloride, post-treatment is also necessary, that is, it must go through alkali washing, water washing and hot air drying processes; the purpose of alkali washing and water washing is to remove low molecular weight polymers mixed in the polymer and a small amount of residual dispersant gelatin and other impurities, because these substances are substances that seriously affect the thermal stability of polyvinyl chloride; alkali treatment generally uses a 0.1% sodium hydroxide aqueous solution, the treatment temperature is controlled at 90°C, and an air compressor is used for blowing for 2 hours; free alkali is removed with water, and finally hot air is dried at about 80°C to obtain modified PVC.
[0078] The modified glass fiber preparation method is as follows:
[0079] XI: 17.0 g of glass fiber is immersed in 100 mL of 5% hydrofluoric acid aqueous solution for 30 seconds, and then cleaned and dried for later use;
[0080] X2: The glass fiber of step (1) is mixed with 2.2 g of dimethoxymethylvinylsilane, 1.5 g of methyltriethoxysilane, 100 mL of toluene, and 1.2 g of 1.0 mol / L phosphoric acid at 70° C. for 2.5 h to obtain modified glass fiber.
[0081] Comparative Example 1
[0082] A method for preparing a hot-pressed PVC floor comprises the following steps:
[0083] S1: 33 g of PVC resin, 17 g of modified glass fiber, 3.3 g of diisooctyl phthalate, 7.0 g of dibutyl phthalate, 6.1 g of calcium zinc stabilizer, 27.5 g of calcium carbonate, 2.2 g of chlorinated paraffin, 2.2 g of stearic acid, 5.0 g of polyvinyl alcohol, 8.0 g of vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer, and 1.1 g of trinonylphenyl phosphite were pre-mixed in a mixer at a mixing speed of 900 r / min for 20 min. The uniformly mixed raw materials were extruded using a twin-screw extruder and hot-pressed at 90° C. to obtain a PVC floor substrate.
[0084] S2 is to stack and pave a PVC floor substrate with a thickness of 3.9 mm and a PVC wear-resistant layer with a thickness of 0.6 mm;
[0085] S3 is hot-pressed at a temperature of 90°C and a pressure of 13MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor; the density is 1.8g / cm 3 .
[0086] The preparation method of the modified glass fiber is the same as that of Example 1, which will not be repeated here.
[0087] Comparative Example 2
[0088] A method for preparing a hot-pressed PVC floor comprises the following steps:
[0089] S1: 50 g of modified PVC resin, 3.3 g of diisooctyl phthalate, 7.0 g of dibutyl phthalate, 6.1 g of calcium zinc stabilizer, 27.5 g of calcium carbonate, 2.2 g of chlorinated paraffin, 2.2 g of stearic acid, 5.0 g of polyvinyl alcohol, 8.0 g of vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer, and 1.1 g of trinonylphenyl phosphite were pre-mixed in a mixer at a mixing speed of 900 r / min for 20 min. The uniformly mixed raw materials were extruded using a twin-screw extruder and hot-pressed at 90° C. to obtain a PVC floor substrate.
[0090] S2 is to stack and pave a PVC floor substrate with a thickness of 3.9 mm and a PVC wear-resistant layer with a thickness of 0.6 mm;
[0091] S3 is hot-pressed at a temperature of 90°C and a pressure of 13MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor; the density is 1.8g / cm 3 .
[0092] The preparation method of the modified PVC resin is the same as that of Example 1, which will not be repeated here.
[0093] Comparative Example 3
[0094] A method for preparing a hot-pressed PVC floor comprises the following steps:
[0095] S1: pre-mix 36.3 g of modified PVC resin, 17 g of modified glass fiber, 7.0 g of dibutyl phthalate, 6.1 g of calcium zinc stabilizer, 27.5 g of calcium carbonate, 2.2 g of chlorinated paraffin, 2.2 g of stearic acid, 5.0 g of polyvinyl alcohol, 8.0 g of vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer, and 1.1 g of trinonylphenyl phosphite by a mixer at a mixing speed of 900 r / min and a mixing time of 20 min. The uniformly mixed raw materials are extruded by a twin-screw extruder and hot-pressed at 90° C. to obtain a PVC floor substrate;
[0096] S2 is to stack and pave a PVC floor substrate with a thickness of 3.9 mm and a PVC wear-resistant layer with a thickness of 0.6 mm;
[0097] S3 is hot-pressed at a temperature of 90°C and a pressure of 13MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor; the density is 1.8g / cm 3 .
[0098] The preparation method of the modified glass fiber and the preparation method of the modified PVC resin are the same as those in Example 1 and will not be described in detail here.
[0099] Test items:
[0100] The test of heating dimensional change rate was carried out in accordance with "GB / T 4085-2015 Semi-rigid PVC Block Flooring". The above-mentioned Example 1 and Comparative Examples 1-3 were placed in an oven at 80°C for 6 hours and then taken out, placed under standard conditions for 24 hours, and then the distance between the markings of each test piece was measured, and the longitudinal and transverse heating dimensional change rates of each test piece were calculated respectively.
[0101] The above Example 1 and Comparative Examples 1-3 were subjected to floor warping test. The normal temperature warping test conditions were 23±2°C and 50±5% humidity; the heated warping test was also conducted in accordance with GB / T 4085-2015 Semi-rigid polyvinyl chloride block flooring, 80°C, 6h standard.
[0102] According to the requirements of "GB / T 4085-2015 Semi-rigid polyvinyl chloride block floor", Example 1 and Comparative Examples 1-3 were tested in a dent tester, and the thickness gauge measured the thickness t0 of the calibration point, applied a pressure of (133±1)N, started timing within 2s, maintained for (540±2)s, then removed all loads, and measured the thickness t1 of the marked point, accurate to 0.01mm. The arithmetic mean of the residual dents is expressed as follows:
[0103] D=t0-t1
[0104] Where:
[0105] D——residual depression, in millimeters (mm);
[0106] t0——the thickness of the specimen before loading, in millimeters (mm);
[0107] t1——the thickness of the specimen after the load is removed, in millimeters (mm);
[0108] According to the requirements of GB / T 4085-2015 Semi-rigid polyvinyl chloride block flooring, the wear resistance grades of Example 1 and Comparative Examples 1-3 under the standard test method are expressed.
[0109] a) The specimen is adjusted to constant weight under standard test conditions. If the mass change within 24 hours is less than 0.002g, it is considered to have reached constant weight.
[0110] b) Wear-resistant layer density test: Take three 30mm×30mm wear-resistant layer specimens from the three 100mm×100mm specimens and perform density test according to the immersion method specified in GB / T 1033.1-2008;
[0111] The density of the specimen is expressed as the arithmetic mean of the density of the wear-resistant layer specimen tested, accurate to 0.001 g / cm 3 .
[0112] c) Weigh the other three specimens separately and record them as the initial mass of the specimens m0, accurate to 0.1 mg;
[0113] d) Fix the specimen on the test bench, place two grinding wheels on the specimen, apply a load of (9.8±0.1)N, and place a vacuum cleaner above the specimen. Fill the container with abrasive, open the sand drop pipe, and the abrasive drop speed is (21±3)g / min. Abrasive should be added in time during the test to ensure the test is carried out normally.
[0114] e) Subject the specimen to a 5000-turn wear test. If the wear-resistant layer of the first specimen is not worn through before 5000 turns, weigh the specimen directly and measure the other two specimens. If the wear-resistant layer of the first specimen is worn through before 5000 turns, discard it and measure the other two specimens. Pause the test every 200 turns, remove the specimen, gently wipe off the particles on the surface of the specimen with a dry and soft cloth, and weigh the specimen to an accuracy of 0.1 mg. Continue grinding until 2000 turns or stop the test when the wear-resistant layer is worn through.
[0115] The volume loss F of each specimen after 100 turns of wear is calculated according to the following formula: V The results are expressed as the arithmetic mean of all test pieces, accurate to 0.1 mm. 3 .
[0116] F V=[(m0-m1) / (nρ)]×100
[0117] F V ——Volume loss of the specimen after 100 revolutions of wear resistance, in cubic millimeters (mm 3 );
[0118] m0——initial mass of the specimen, in milligrams (mg);
[0119] m1——The weight of the last weighing or the weighing before grinding, in milligrams (mg);
[0120] n——total number of revolutions;
[0121] The above-mentioned Example 1 and Comparative Examples 1-3 were subjected to impact strength tests according to the national standard "GB / T1043.1-2008 Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test".
[0122] Table 1 is about the physical performance parameters of hot-pressed PVC floor
[0123] Experimental Project index Heating dimensional change rate / % ≤0.25 Heating warpage / mm ≤2 <![CDATA[Wear resistance (volume loss F V ) n / mm 3 , class T]]> <![CDATA[F V ≤2.0]]> <![CDATA[Wear resistance (volume loss F V ) n / mm 3 , P grade]]> <![CDATA[2<F V ≤4]]> <![CDATA[Wear resistance (volume loss F V ) n / mm 3 , class M]]> <![CDATA[4<F V ≤7.5 <!-- 9 -->]]> <![CDATA[Wear resistance (volume loss F V ) n / mm 3 , class F]]> <![CDATA[7.5<F V ≤15.0]]> <![CDATA[Residual depression I R / mm]]> <![CDATA[0.15<I R ≤0.40]]> Impact resistance All specimens had no cracks outside the test range
[0124] Table 2 Test results of various performance parameters of hot-pressed PVC floor
[0125]
[0126] According to Table 2 above, by comparing Example 1 with Comparative Examples 1-2, it can be seen that the modified PVC and whether or not to add modified glass fiber have a significant impact on the various properties of the hot-pressed PVC floor. The reason is that in the hot-pressed PVC floor, the mechanism by which the ultra-large molecular weight PVC improves the PVC floor is mainly achieved by improving the toughness and impact strength of PVC. Specifically, the ultra-large molecular weight PVC can reduce the free volume of the PVC chain segment, thereby reducing its stress concentration during the deformation process and improving its energy absorption capacity.
[0127] In addition, ultra-high molecular weight PVC can also increase the flexibility of the PVC chain, reduce the stress concentration between its crystalline and amorphous regions, and further improve its toughness. By using ultra-high molecular weight PVC, the impact strength and wear resistance of PVC flooring can be effectively improved, thereby increasing its service life and comfort.
[0128] At the same time, ultra-large molecular weight PVC can also improve the dimensional stability and thermal stability of PVC flooring, allowing it to maintain stable performance under changing temperature and humidity conditions.
[0129] The strength of the glass fiber is enhanced by corroding it. Comparing Example 1 with Comparative Example 2, it is obvious that after silane modification and continued reaction with vinyl chloride monomer, the notched impact strength can be improved. This is because long polyvinyl chloride molecular chains are generated on the surface of the glass fiber. This structure is similar to the shape of a feather duster. The long polyvinyl chloride chains are distributed on the surface of the glass fiber like chicken feathers, so that the long-chain polyvinyl chloride on the surface of the glass fiber after processing has good compatibility with the polyvinyl chloride matrix resin. It is not like ordinary glass fiber that can hardly fuse with the matrix, nor is it like conventional silane coupling agent modification of the glass fiber surface, which only grafts a small amount of shorter chemical bonds on the surface of the glass fiber, making the glass fiber unable to achieve complete compatibility with the polyvinyl chloride matrix.
[0130] By comparing Example 1 and Comparative Example 3, it can be seen that diphenyl isooctyl phosphate can improve various properties of PVC flooring. The possible reasons are: diphenyl isooctyl phosphate can effectively improve the toughness, hydrophilicity, stretchability and heat resistance of modified polyvinyl chloride, and diphenyl isooctyl phosphate and modified polyvinyl chloride have good compatibility. Diphenyl isooctyl phosphate (DPOP) is a commonly used industrial colorless, transparent, oily liquid plasticizer with good compatibility with polymers. Adding diphenyl isooctyl phosphate can effectively improve the flexibility, hydrophilicity and thermal stability of polyvinyl chloride plastics. The higher the mass fraction of diphenyl isooctyl phosphate, the better the flexibility of the modified polyvinyl chloride sample, the stronger the hydrophilicity of the modified polyvinyl chloride film, and the stronger the thermal stability. Diphenyl isooctyl phosphate can change the glass transition temperature of modified polyvinyl chloride. In general, diphenyl isooctyl phosphate (C 20 H 27 O4P) is a colorless, transparent, oily liquid, mainly used as a flame retardant plasticizer. It is compatible with almost all major industrial resins and rubbers, and has better compatibility with modified polyvinyl chloride. It has low volatility, good plugging resistance and weather resistance. When used in combination with phthalate plasticizers, it can improve the toughness and weather resistance of the product; when used in modified polyvinyl chloride films, it can improve tensile strength and improve wear resistance and moisture resistance.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Modifications, replacements, and improvements made within the principles of the present invention should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a hot-pressed PVC floor, characterized in that: It includes the following components, by weight: S1: pre-mix 20-33 parts of modified PVC resin, 10-20 parts of modified glass fiber, 3-5 parts of diphenyl ethyl phosphate, 5-10 parts of plasticizer, 5-8 parts of stabilizer, 20-30 parts of filler, 2-3 parts of internal lubricant, 2-3 parts of external lubricant, 3-5 parts of polyvinyl alcohol, 3-10 parts of processing aid, and 1-2 parts of antioxidant in a mixer at a mixing speed of 800-1000 r / min and a mixing time of 20-30 min. The uniformly mixed raw materials are extruded by a twin-screw extruder and hot-pressed at 80-140° C. to form a PVC floor substrate. S2 is to stack and pave the PVC floor substrate with a thickness of 3.0~5.4 mm and the PVC wear-resistant layer with a thickness of 0.1~1.0 mm; S3 hot pressing and forming at a temperature of 80-140° C. and a pressure of 10-20 MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot pressing formed PVC floor; The modified PVC resin preparation method is as follows: (1) Add vinyl chloride, initiator, chain extender, dispersant, granulating agent, 20-40% by mass hydrogen peroxide aqueous solution, and 20-40% by mass sodium hydroxide aqueous solution into water and mix and stir at a stirring rate of 400-600 r / min for 10-20 min; (2) Continue heating to 30-60°C, add 30-50% sodium sulfide aqueous solution, and carry out polymerization reaction at a pressure of 1-3 MPa to obtain ultra-high molecular weight polyvinyl chloride; (3) Continue to go through the steps of alkali washing, water washing and hot air drying, wherein the alkali treatment uses a sodium hydroxide aqueous solution with a concentration of 0.1-0.2%, the treatment temperature is controlled at 85-90°C, and an air compressor is used to blow for 1-2 hours; the free alkali is removed with water, and finally hot air is dried at 70-90°C to obtain the modified PVC resin; The modified glass fiber preparation method is as follows, in parts by weight: X1 Immerse 10-20 parts of glass fiber in 50-100 mL of 3-5% hydrofluoric acid aqueous solution for 20-50 seconds, continue to clean and dry, and set aside; X2: The glass fiber of step X1 is mixed with 2-3 parts of alkoxysilane, 1-2 parts of end-capping agent, 50-100 mL of organic solvent, and 1-2 parts of catalyst at 40-80° C. for 2-3 hours to obtain a modified glass fiber; the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and di(2-ethylhexyl)peroxydicarbonate; The granule is at least one of sorbitol laurate and n-butyl chloroformate; The plasticizer is at least one of dioctyl phthalate, dibutyl phthalate, dioctyl adipate, polybutylene adipate, polybutylene adipate-1,4-adipate, chlorinated paraffin, epoxidized soybean oil, and 3-hydroxy-3-carboxy tributyl glutarate; The processing aid is at least one of acrylic copolymers, chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymers, and vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomers; The alkoxysilane is at least one of dimethoxymethylvinylsilane, vinyltriethoxysilane, acryltriethoxysilane and phenyltriethoxysilane; the end-capping agent is at least one of hexamethyldisiloxane, methyltriethoxysilane and tetramethyldivinyldisiloxane.
2. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The chain extender is at least one of 1,4-butanediol, 1,6-hexanediol, diallyl phthalate and diallyl maleate; the dispersant is at least one of gelatin, polyvinyl alcohol and calcium alkylbenzene sulfonate.
3. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The glass fiber has a diameter of 20-60 μm and a length of 50-300 mm.
4. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The organic solvent is at least one of tetrahydrofuran, methanol, toluene, n-hexane and chloroform; the catalyst is at least one of sulfuric acid, phosphoric acid, hydrochloric acid and perchloric acid.
5. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The catalyst molar concentration is 0.8-2.5 mol / L.
6. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The stabilizer is at least one of a calcium zinc stabilizer, a rare earth stabilizer, and an organic tin stabilizer; the filler is at least one of calcium oxide, calcium carbonate, precipitated barium sulfate, and silicon dioxide; the internal lubricant is at least one of chlorinated paraffin and glyceryl triacetylhydroxystearate; the external lubricant is at least one of stearic acid, silicone powder, methyl stearate, propyl stearate, and butyl stearate; the antioxidant is at least one of antioxidant 1010, antioxidant 168, 2,6-di-tert-butyl-p-cresol, N,N'-di-sec-butyl-p-phenylenediamine, and trinonylphenyl phosphite.
7. The method for preparing a hot-pressed PVC floor according to claim 1, characterized in that: The following steps are involved: S1: 33 g of modified PVC resin, 17 g of modified glass fiber, 3.3 g of diisooctyl phthalate, 7.0 g of dibutyl phthalate, 6.1 g of calcium zinc stabilizer, 27.5 g of calcium carbonate, 2.2 g of chlorinated paraffin, 2.2 g of stearic acid, 5.0 g of polyvinyl alcohol, 8.0 g of vinyl chloride-butyl acrylate-methyl methacrylate copolymer elastomer, and 1.1 g of trinonylphenyl phosphite were pre-mixed in a mixer at a mixing speed of 900 r / min and a mixing time of 20 min. The uniformly mixed raw materials were extruded using a twin-screw extruder and hot-pressed at 90°C to obtain a PVC floor substrate; S2 is to stack and pave a PVC floor substrate with a thickness of 3.9 mm and a PVC wear-resistant layer with a thickness of 0.6 mm; S3 is hot-pressed at a temperature of 90°C and a pressure of 13 MPa to complete the bonding process between the wear-resistant layer and the substrate to obtain the hot-pressed PVC floor; the density is 1.8 g / cm 3 ; The preparation method of the modified PVC resin is: (1) Add 33 g vinyl chloride, 6.6 g azobisisobutyronitrile, 1.4 g diallyl phthalate, 0.02 g gelatin, 0.5 g n-butyl chloroformate, 0.02 g 30% aqueous hydrogen peroxide solution, and 0.5 g 30% aqueous sodium hydroxide solution into 50 mL water and stir at a stirring rate of 400 r / min for 10 min. (2) Continue heating to 38°C, add 0.5 g of 50% sodium sulfide aqueous solution, and polymerize at a pressure of 2 MPa to obtain ultra-high molecular weight polyvinyl chloride; (3) After alkali washing, water washing and hot air drying, the alkali treatment uses a 0.1% sodium hydroxide aqueous solution, the treatment temperature is controlled at 90°C, and an air compressor is used to blow for 2 hours; the free alkali is removed with water, and finally dried with hot air at 80°C to obtain the modified PVC; The modified glass fiber preparation method is as follows: XI: 17.0 g of glass fiber was immersed in 100 mL of 5% hydrofluoric acid aqueous solution for 30 seconds, and then cleaned and dried for later use; X2: The glass fiber prepared in step (1) was mixed with 2.2 g of dimethoxymethylvinylsilane, 1.5 g of methyltriethoxysilane, 100 mL of toluene, and 1.2 g of 1.0 mol / L phosphoric acid at 70°C for 2.5 h to obtain modified glass fiber.
8. A thermoformed PVC floor, characterized by: Prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
A hot-pressing method for PVC composite flooring and PVC composite flooring
CN112428653B
Polyvinyl chloride production method adding chain extender to match with later-stage heating process
CN103360536A
High-strength glass fiber modified polyvinyl chloride material floor and preparation method thereof
CN108485116A
High-stability hot press molding floor and preparation method thereof
CN114347601A